1977
DOI: 10.1007/bf00508636
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intraperitoneally administered GABA on brain monoamine metabolism

Abstract: GABA was injected intraperitoneally to rats in single doses of 2.5 to 1500 mg/kg. Thirty minutes after injection a dose-dependent increase in dopamine (DA) and a decrease in noradrenaline (NA) content were observed in the brain. However, in the lowest dose range these levels showed small but significant changes in the opposite direction. The accumulation of dopa after inhibition of the aromatic L-aminoacid decarboxylase was enhanced by i.p. GABA both in DA- and in NA-predominated brain regions, the dose-respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…It has been reported that GABA, progabide, and fengabine induce norepinephrine neuronal activity in rat brains. [41][42][43][44] GABA A and GABA B receptor activation may, respectively, increase and decrease norepinephrine release in rat cortex and hippocampus, [45][46][47] whereas baclofen reduced adrenergic binding sites. 48 Also, norepinephrine increased GABA inhibitory transmission in human cerebral cortex, probably via a-adrenergic receptors, 49 and in rat cerebellar cortex.…”
Section: Gabaergic Modulation Of Neuronal Activitymentioning
confidence: 99%
“…It has been reported that GABA, progabide, and fengabine induce norepinephrine neuronal activity in rat brains. [41][42][43][44] GABA A and GABA B receptor activation may, respectively, increase and decrease norepinephrine release in rat cortex and hippocampus, [45][46][47] whereas baclofen reduced adrenergic binding sites. 48 Also, norepinephrine increased GABA inhibitory transmission in human cerebral cortex, probably via a-adrenergic receptors, 49 and in rat cerebellar cortex.…”
Section: Gabaergic Modulation Of Neuronal Activitymentioning
confidence: 99%
“…It is well-established that the removal of the inhibitory dopaminergic control stimulates PRL secretion (Tuomisto & Mannisto 1985;Moore 1987). On the other hand, GABA and several GABA agonists such as muscimol and baclofen elevate the cerebral concentration of dopamine (DA) and its acidic metabolites, enhance the, formation of dopa, and decelerate the a-methyl-p-tyrosine (aMT)-induced depletion of DA which findings indicate that they increase the synthesis but decrease the utilization of DA (AndCn 1977;AndCn et al 1978;Biswas & Carlsson 1977a & b;Biggio et al 1977;Waldmeier & Maitre 1978;Wood 1982). Garcia de Yebenes Prous et al (1978) found that intracerebroventricular taurine caused similar effects to those of intracerebroventricular GABA, and suggested that these compounds inhibit the firing of dopaminergic neurones.…”
mentioning
confidence: 99%
“…Dihydroxyphenylalanine (DOPA) is a precursor for the synthesis of both dopamine and norepinephrine in brain tissue, and the measurement of the rate of accumulation of DOPA in brain after inhibition of aromatic amino acid decarboxylase has been utilized as an estimate of in vivo rates of dopamine or norepinephrine synthesis (Biswas and Carlsson, 1977;Liljequist et al, 1977). At present, brain DOPA levels are measured primarily by the method of Kehr et al (1972), in which DOPA is isolated by use of anion exchange chromatography and quantitated fluorimetrically after conversion t o a hydroxyindole compound.…”
mentioning
confidence: 99%